Türkiye’de ve Güney Kore’de okul öncesi eğitimin incelenmesi - Choi, Jeongsuk (My University, 2013)
TÜRKİYE’DE VE GÜNEY KORE’DE OKUL ÖNCESİ EĞİTİMİN İNCELENMESİ Türkiye’de ve Güney Kore’de okul öncesi eğitimin incelenmesi isimli bu çalışmanın birinci boyutunda; iki ülkenin eğitim programlarının dayandığı felsefe, amaçları ve hedefleri, içerikleri, eğitim durumları ve değerlendirmeleri, ikinci boyutunda; eğitim ortamları, üçüncü boyutunda ise, okul öncesi öğretmenlerin yetiştirilme biçimleri ve mesleki özelliklerine bakılmıştır. Gerekli literatür taraması araştırmacı tarafından Türkiye ve Güney Kore’de bulunan kütüphanelerde gerçekleştirilmiştir. Araştırmanın çalışma grubu Türkiye’nin İstanbul ilindeki farklı ilçelerden tesadüfî yöntemle seçilmiş 25, Güney Kore’nin Seul ilindeki farklı bölgelerden tesadüfî yöntemle seçilmiş 25 devlet ve özel okul öncesi eğitimi kurumu olmak üzere toplam 50 okul ve bu kurumlarda çalışan 57 okul öncesi öğretmeninden (27 Türk, 30 Koreli) oluşmaktadır. Araştırmanın sonucunda elde edilen bulgular doğrultusunda Türkiye’de ve Güney Kore’de eğitim programları açısından her iki ülkedeki okul öncesi eğitim programlarının gelişiminde değişik yollar takip edildiği görülmüştür. Güney Kore okul öncesi eğitim programının çok revize edildiği ve bu revize çalışmalarının yapıldığı dönemlerin özelliklerinin programın amaçları, hedefleri ve içeriklerine yansıtıldığı anlaşılmıştır. Türkiye’de ise, kalkınma dönemleri ile birlikte okul öncesi eğitim programında değişiklikler yapılmıştır. Okul öncesi eğitimin dayandığı felsefenin, Türkiye’de “alp insan tipi”, Güney Kore’de ise “hongik ingan tipi” nin olduğu saptanmıştır. Eğitim ortamları açısından bakıldığında, iki ülkenin okul öncesi eğitim ortamlarının paralel özellikler gösterdiği anlaşılmıştır. Her iki ülkedeki okul öncesi eğitim kurumlarında çalışan öğretmenlerin yetiştirilme biçimleri ve mesleki özelliklerine bakıldığında benzerlikler taşıdıkları görülmüştür. Anahtar Sözcükler: Okul Öncesi Eğitim, Türkiye’de Okul Öncesi Eğitim Programları ve Eğitim Ortamları, Güney Kore’de Okul Öncesi Eğitim Programları ve Eğitim Ortamları. Türkiye’de Okul Öncesi Öğretmenlerin Mesleki Özellikleri, Güney Kore’de Okul Öncesi Öğretmenlerin Mesleki Özellikleri.

A STUDY OF THE PRESCHOOL EDUCATION IN TURKEY AND SOUTH KOREA In the first dimension of this study which is titled the examination of the preschool education in Turkey and South Korea; the philosophy on which the educational programs of both of the countries, its purposes and targets and contents are examined, and in the second dimension; the educational environments are examined and in the third dimension, the preschool teacher training methods and the professional characteristics of the teachers are examined. The necessary literature study is carried out in the libraries situated in Turkey and South Korea by the researcher. The workgroup of the study is composed of 25 preschool educational institutions which are selected by random method from different districts in Istanbul province of Turkey, 25 state and private preschool educational institutions which are selected by random method from different regions of Seoul province of South Korea and a total of 50 schools and 57 preschool teachers who are employed in these organizations (27 Turkish teachers and 30 Korean teachers). It is seen that different ways are followed in the development of the preschool educational programs in both countries in terms of the educational programs in Turkey and in South Korea in accordance with the findings which are obtained as a result of the study. It is understood that the preschool educational programs are much revised in South Korea and the characteristics of the periods in which such revision studies are carried out are reflected on the purposes, targets and contents of the program in question. In Turkey, some changes are made in the preschool educational programs together with the development periods. It is determined that the philosophy on which the preschool education is based is “alp human type” in Turkey and “hongik ingan type” in Korea. When it is examined in terms of the educational environments, it is understood that the preschool educational environments of both of the countries show parallel characteristics. Whenever the training methods and professional characteristics of the teachers who are employed in the preschool educational institutions in both of the countries are examined, it is seen that they have some similarities. Preschool Education, Preschool Education Programs and Educational Environments in Turkey, Preschool Education Programs and Educational Environments in South Korea. Professional Characteristics of the Preschool Teachers in Turkey and the Professional Characteristics of the Preschool Teachers in South Korea.
Keywords: Eğitim, İlk; Güney Kore; Türkiye